Medicare Part B and Part D drug eligibility for center for Medicare and Medicaid Services price negotiation under the Inflation Reduction Act: estimates using 2016-2019 data - Omar Qureshi; Reshma Ramachandran; Joseph S. Ross (Taylor & Francis Group, 2024)
ABSTRACTBackground To reduce Medicare prescription drug expenditures, the 2022 Inflation Reduction Act (IRA) allows the Centers for Medicare & Medicaid Services (CMS) to directly negotiate with drug manufacturers on Medicare prices of high-expenditure drugs (≥$200m annual spending) which meet certain eligibility criteria. However, it is unclear what proportion of high-expenditure drugs covered by Medicare, and attributable annual drug spending, would typically be eligible for CMS negotiations in a given year.Methods We used historical Medicare drug spending data to determine how many high-expenditure drugs, and attributable drug spending, would have been eligible for CMS negotiations had the IRA been in effect from 2016-2019, while also determining which of the IRA's eligibility criteria is most restrictive.Results From 2016-2019, approximately one third (33.3% for Part B, 32.4% for Part D) of high-expenditure Medicare drugs would have been eligible for negotiation, with ineligible drugs accounting for 75.2% and 63.8% of spending on high-expenditure drugs in Medicare Part B and D, respectively. Most ineligible high-expenditure drugs were ineligible because they launched too recently. From 2016-2019, between 59 and 74 high-expenditure drugs were eligible per year, indicating that in some years there may not be enough eligible drugs for CMS to negotiate on the maximum number of drugs allowable by law.Conclusions The IRA's current eligibility criteria may restrict CMS from being able to negotiate drug prices on approximately two-thirds of the high-expenditure drugs covered by Medicare and may not allow CMS to negotiate on the maximum number of drugs allowable by law. Congress could consider relaxing eligibility requirements for price negotiation, such as those pertaining to launch date recency, to ensure there are a sufficient number of high-expenditure drugs eligible for negotiation or make certain ineligible drugs contributing to significant annual Medicare spending eligible for negotiation on a case-by-case basis.